2020
DOI: 10.1111/sed.12775
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical fingerprints of dolomitization in Bahamian carbonates: Evidence from sulphur, calcium, magnesium and clumped isotopes

Abstract: In an effort to constrain the mechanism of dolomitization in Neogene dolomites in the Bahamas and improve understanding of the use of chemostratigraphic tracers in shallow-water carbonate sediments the δ 34 S, Δ 47 , δ 13 C, δ 18 O, δ 44/40 Ca and δ 26 Mg values and Sr concentrations have been measured in dolomitized intervals from the Clino core, drilled on the margin of Great Bahama Bank and two other cores (Unda and San Salvador) in the Bahamas. The Unda and San Salvador cores have massively dolomitized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 114 publications
0
31
0
Order By: Relevance
“…Because of this, in order to successfully fingerprint dolomite without the potential bias of later‐stage recrystallization expected from using either Δ 47 and/or δ 18 O, the identification of the conditions in which dolomite forms must rely on the informed application of multiple isotopic systematics capable of constraining rock versus fluid buffering systems (e.g. Ahm et al ., 2018; Murray et al., 2021). In addition, newer understanding of rock buffering of porewater composition, especially in the zone marked by dissolution of aragonite and VHMC, such as in the phreatic meteoric zone, could also bias the stable isotopic signal (Banner & Hanson, 1990; Higgins et al ., 2018).…”
Section: Detecting Biogeochemical Signatures Of Mixing‐zone Dolomitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this, in order to successfully fingerprint dolomite without the potential bias of later‐stage recrystallization expected from using either Δ 47 and/or δ 18 O, the identification of the conditions in which dolomite forms must rely on the informed application of multiple isotopic systematics capable of constraining rock versus fluid buffering systems (e.g. Ahm et al ., 2018; Murray et al., 2021). In addition, newer understanding of rock buffering of porewater composition, especially in the zone marked by dissolution of aragonite and VHMC, such as in the phreatic meteoric zone, could also bias the stable isotopic signal (Banner & Hanson, 1990; Higgins et al ., 2018).…”
Section: Detecting Biogeochemical Signatures Of Mixing‐zone Dolomitesmentioning
confidence: 99%
“…A more extended use of the isotopic composition of carbonate associated sulphate (CAS) can shed an additional light onto mixing‐zone diagenesis. This latter proxy has been applied to great effect in constraining conditions during the early diagenetic history of marine sediments (Rennie & Turchyn, 2014; Present et al ., 2015; Murray et al., 2021), and recently to the analysis of diagenetic porewaters in the Permian carbonates of the Guadalupian Mountains (Present et al ., 2019). Iron isotope systematics provide another redox sensitive proxy exhibiting a non‐conservative behaviour across mixing zones (Rouxel et al ., 2008).…”
Section: Detecting Biogeochemical Signatures Of Mixing‐zone Dolomitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagenetic processes may exchange sulfate with the primary carbonate and alter its isotopic composition (Fichtner et al, 2017;Murray et al, 2020;Present et al, 2015Present et al, , 2019. Kampschulte & Strauss (2004) suggested that the variability of multiple δ 34 S analyses from contemporaneous stratigraphic successions could be used to quantify the effect of diagenesis on the CAS record.…”
Section: Carbonate-associated Sulfatementioning
confidence: 99%
“…Carbonates recrystallizing during burial may also be prone to diagenetic modification of the δ 34 S of CAS if the burial fluids were sulfate rich (Fichtner et al, 2017(Fichtner et al, , 2018Present et al, 2015). The δ 34 S in burial fluids may be highly variable, and include sulfate from hydrocarbon or organic matter degradation, dissolved evaporites, groundwater modified by MSR, or sulfate released by dissolution of CAS (Dogramaci et al, 2001;Fichtner et al, 2018;Murray et al, 2020;Present et al, 2019;Thode & Monster, 1965, 1970.…”
Section: Carbonate-associated Sulfatementioning
confidence: 99%